The Relevance and Contribution of Al Ghazali's Thought in Islamic Business Ethics: An Overview - Suherli, Ian Rakhamawan; Ridwan, Ahmad Hasan; Kusuma, Nurul Rahmah; Qarni, Muhammad Al; Azzahro, Naufi Fajria; Sutira, Andri (ITB AAS INDONESIA Surakarta, 2023)
Ethics in business, can be interpreted by learning about the difference between good and right with bad and wrong in the business environment based on moral values added to halal rules and then haram, then Islam interprets business ethics as a collection of ethical attitudes and behaviors of business that are based on religious teachings by prioritizing halal and haram first. General provisions in thinking, especially business ethics according to Islam which is a science contained in the Qur'an and Al Hadith, which needs to be used as the main reference by all Islamic business actors so that in carrying out activities not only oriented to get world prosperity but also obtain prosperity hereafter. Al Ghazali has conveyed the basic principles in an effort to obtain worldly wealth as well as the Hereafter, namely with the instructions he gave on how to behave in business, basically adapted to the guidance of Islamic teachings both the Qur'an and As Sunnah or Al Hadith.